(untitled) (International Journal of Engineering and Computer Science, 2016)
Cloud Computing is a remote location technology which provides Platform as a Service (PaaS), Software as a Service (SaaS) and Infrastructure as a Service (IaaS). High Performance Computing (HPC) allows scientists and engineers to solve complex science, engineering, and business problems using applications that require high bandwidth, enhanced networking, and very high compute capabilities. The combination of Cloud Computing and High Performance Computing allows you to increase the speed of research by running high performance computing in the cloud and to reduce costs by providing Cluster Compute or Cluster GPU server’s on-demand without large capital investments. Tap into unlimited resources to scale your High Performance Computing jobs - analyzing large-scale data, running simulations and financial models and experimenting while reducing time to market. Build your personalized end to end High Performance Computing solution on Cloud which tailored to your organization’s needs.